The dehesa: an agrosilvopastoral system of the Mediterranean region with special reference to the Sierra Morena area of Spain (Agroforestry Systems, 1988)
A multidisciplinary team undertook a six-year investigation on the agro-ecological and socio-economic aspects of the dehesa system in the Sierra Norte area, a part of the Sierra Morena of the Sevilla Province, Western Andalusia, Spain. This paper summarizes its findings on the various agro-ecological features of the system and evaluates the system's functional aspects vis-a-vis the trends and developments in land use in the region over the past few centuries. The synergistic effects of tree cover on understorey grassland vegetation is discussed in terms of soil fertility build-up and favourable micro-climatic and hydrological features, and the potential use of this information in future research and development programmes to improve the dehesa system in the Mediterranean region is outlined.